New secondary metabolites produced by the phytopathogenic fungus Wilsonomyces carpophilus. (August 2018) - Narmani, Abolfazl; Teponno, Rémy Bertrand; Arzanlou, Mahdi; Babai-Ahari, Asadollah; Stadler, Marc
Graphical abstract: Highlights: The phytopathogenic fungus Wilsonomyces carpophilus was studied for secondary metabolite production. Two unusual pseurotin (1-oxa-7-azaspiro[4.4]non-2- ene-4, 6-dione) derivatives were found. Their chemical structures were elucidated by 2D-NMR, HR-MS and CD spectroscopy. Abstract: Two new metabolites possessing the unusual 1-oxa-7-azaspiro[4.4]non-2- ene-4, 6-dione core (2, 3 ) along with the recently described pseurotin A3 (1 ) were isolated from the pathogenic fungus Wilsonomyces carpophilus ( previously named Stigmina carpophila ). The producer organism was obtained from Prunus armeniaca collected in Iran and was identified by morphological and molecular phylogenetic methods. The structures of the isolated compounds were elucidated on the basis of extensive NMR spectroscopic analysis, high-resolution mass spectrometry and ECD analysis. The compounds were screened for their antimicrobial, cytotoxic, nematicidal and biofilm inhibition activities but, no significant effect was observed. To the best of our knowledge, this is the first report on the isolation of secondary metabolites produced by W. carpophilus .